2018
DOI: 10.3389/fphar.2018.01451
|View full text |Cite
|
Sign up to set email alerts
|

Moral Attitudes Toward Pharmacological Cognitive Enhancement (PCE): Differences and Similarities Among Germans With and Without PCE Experience

Abstract: Pharmacological cognitive enhancement (PCE), the use of illicit and/or prescription drugs to increase cognitive performance, has spurred controversial discussion in bioethics. In a semi-structured interview study with 60 German university students and employees, differences and similarities in moral attitudes toward PCE among 30 experienced participants (EPs) vs. 30 inexperienced participants (IPs) were investigated. Substances EPs used most often are methylphenidate, amphetamines, tetrahydrocannabinol and mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
4
0
1
Order By: Relevance
“…Similarly, in a study by Pighi et al (2018) almost a third of the Italian medical students found studying stressful (9). The gender implications found in our study have also been seen in several previous studies (27)(28)(29)(30), and the authors explained that this was due to the differences in the social roles assigned to men and women, as well as due to the increased emotional vulnerability of women (23,29). Furthermore, in our study, economic students, compared to medical students, had a lower last exam grade and a significantly higher WTAS score.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, in a study by Pighi et al (2018) almost a third of the Italian medical students found studying stressful (9). The gender implications found in our study have also been seen in several previous studies (27)(28)(29)(30), and the authors explained that this was due to the differences in the social roles assigned to men and women, as well as due to the increased emotional vulnerability of women (23,29). Furthermore, in our study, economic students, compared to medical students, had a lower last exam grade and a significantly higher WTAS score.…”
Section: Discussionsupporting
confidence: 89%
“…Studies have shown that university students use neuroenhancing substances not only for cognitive enhancement, but also to cope with psychosocial stressors (6,23), including exam anxiety which is reported to be a widespread but underestimated and neglected problem (24). In a survey conducted in Germany, more than 50.0% of first and second year, and 70.0% of third, fourth and fifth-year medical students stated that obvious exam anxiety had not been considered by lecturers (25).…”
Section: Introductionmentioning
confidence: 99%
“…Our study employed a cross-sectional design, which limits the possibility of drawing causal inferences. Using a longitudinal design, further studies could examine whether the use of specific cognitive enhancers [ 64 ] predicts additional variance in their ethical judgement towards their use, and whether perception of health risk, effectiveness, legality and knowledge about specific cognitive enhancers predict their use.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that the use of PCE can reach 55% in some fraternities 21 . In the European Union, it is estimated that PCE is adopted by 0.8% to 16% of university students, depending on the country, the university and the drug 10,43,46 . It is difficult, however, to determine the use in European universities, since the samples, methods, and study designs are quite different 10,21 .…”
Section: Academic Use Competitive Fairness and Valorization Of Resultsmentioning
confidence: 99%
“…University students point to the competitive and stressful environment and the feeling of concentration and alertness offered by nootropics as the main reasons for using these substances 19 . Despite this, a clear distinction can be observedespecially in the European context 10,46 -between easy access drugs (such as coffee, caffeine pills, and energy drinks) and prescription cognitive enhancers 21 . The first are commonly found and more prevalent, consumed daily by most students 21 , without social stigma 21,31 , while prescription nootropics have a bad reputation and are sometimes discriminated, as they are seen http://dx.doi.org/10.1590/1983-80422021291449…”
Section: Academic Use Competitive Fairness and Valorization Of Resultsmentioning
confidence: 99%